Feasibility and acceptability of parenting for lifelong health program in Mainland China - Wang, W; Liu, S; Liang, Y; Lachman, JM; Fang, Z; Zhang, H (SAGE Publications, 2023)
Purpose: Parenting for Lifelong Health for Young Children (PLH-YC) is a program to prevent child maltreatment. This study aimed to examine the feasibility, acceptability and preliminary effects of the adapted program for Chinese parents. Methods: A pre–post single-arm pilot trial was conducted with 21 Chinese parents. A mixed-method design was utilized to collect questionnaire-based quantitative data and qualitative data of interviews and focus group discussions. Results: Program implementation was feasible, with overall high recruitment, enrollment, attendance, acceptability and fidelity. Quantitative results demonstrated reductions in general child maltreatment, physical and emotional abuse, child behavioral problems, and improvements in positive parenting. Thematic analyses identified reduced violent discipline, psychological aggression, and child behavioral problems, strengthened parent–child bonds, increased parenting confidence, and decreased family conflict. Conclusion: The adapted PLH-YC program for Chinese parents has shown good feasibility and acceptability, and exhibited a significant association with reduced child maltreatment. Further randomized controlled trials are required.